Imaginary Video Landscape: John Cage, Mugam Music, Video Art (Cinéma & Cie. Film and Media Studies Journal, 2019)
The essays focuses on a video by Robert Cahen and Matias Guerra, Imaginary Video Landscape. For a random number of cuts from 14 archive videos, 2017. This short work, presented in some international festivals, is based on Imaginary Landscape n.5 by John Cage (1952), and offers a profound and interesting intersection between the avant-garde and popular music. Moreover, this “dialogue” is articulated and represented in electronic images by the French video-artist Robert Cahen and the Chilean multimedia artist Matias Guerra. The artists conflate their respective video archives: the images and the music produce a “video landscape” intertwining two different musical experiences, two different approaches and identities. The essay offers a critical analysis of this artwork in relation to John Cage’s influence on video-art, the several existing versions of his musical work, Robert Cahen’s musique concrète as well as to Guerra’s multimedia approach and to the composer Jahangir Selimkhanov’s studies and music inspired by Mugam musical tradition in Azerbaigian.